Challenges and obstacles facing Al-Tahadi schools in the northern Palestinian valleys in Tubas governorate, as seen by the teachers of Al-Tahadi schools (Journal of the College of Basic Education, 2022)
Challenges and obstacles facing Challenge schools in the northern Palestinian valleys in Tubas governorate as seen by the teachers of Challenge schoolsThis study aimed to identify the challenges and obstacles facing the challenge schools in the northern Palestinian valleys, and to highlight the importance of preparing the teacher to meet these challenges and obstacles that face and obstruct these schools.In order to achieve this goal, the researcher followed the descriptive analytical approach, which depends on the opinion poll by studying the phenomenon as it is in reality, and describing it accurately. The quantitative approach was also used to study and analyze data such as rates, percentages and statistical tests. The researcher used two main sources of data as follows:Secondary sources: where the researcher resorted to the secondary data source to address the theoretical framework of the study, through Arabic and foreign books and references, in addition to previous research and studies that dealt with the subject of the current study.Primary sources: It is represented in the questionnaire prepared by the researcher as a main tool for research, as it was distributed to various teachers.The study population consisted of all teachers of Challenge schools in the Directorate of Education / Tubas in the academic year 2021 AD - 2022 AD, and the study sample consisted of (20) individuals distributed on three basic variables, and the study sample was chosen randomly from the members of the original study community.The researcher used the questionnaire as a research tool. In light of the comprehensive review of previous theoretical studies and educational literature related to the subject of the research, and after surveying the opinion of a number of specialists in this field and verifying the validity of the tool, the questionnaire in its final form consisted of 35 paragraphs distributed over four fields.The study reached a set of results, including:* It was found that among the most important challenges and obstacles facing the challenge schools in the northern Palestinian valleys, as seen by the teachers of these schools and related to the student: Weak motivation towards education among students of these schools. Significantly low levels of student achievement. In addition to the poor psychological state of the students due to the presence of the occupation soldiers and settlers.* It was found that among the most important challenges and obstacles facing the challenge schools in the northern Palestinian valleys, as seen by the teachers of these schools and related to the teacher:- Poor qualification of male and female teachers to teach integrated classes. Delaying the appointment of male and female teachers in these schools. And the lack of teachers’ commitment to the times of morning attendance due to the military checkpoints and the distance from schools.* It was found that among the most important challenges and obstacles facing Challenge schools in the northern Palestinian valleys, as seen by the teachers of these schools, related to the environment:- Poor suitability of squares and facilities for students' activities. Lack of educational aids. And the scarcity of a library and laboratory to provide the necessary services for students. In addition to the poor physical environment inside the classrooms (ventilation, lighting, heating and air conditioning).* It turned out that among the most important challenges and obstacles facing the challenge schools in the northern Palestinian valleys, as seen by the teachers of these schools and related to the practices of the Israeli occupation:- Teachers are subjected to humiliation and humiliation by the Israeli occupation soldiers at military checkpoints. In the northern Jordan Valley, the Israeli occupation impedes the arrival of male and female teachers to their schools on time. Teachers often resort to dirt bypass roads because of military checkpoints. Likewise, the occupation partially disrupts work hours due to preventing students and teachers from reaching their schools.* It was also found that there were no statistically significant differences at the significance level (a = 0.05) about the challenges and obstacles facing the challenge schools in the northern Palestinian valleys as seen by the teachers of these schools due to the gender variable.* It was also found that there were no statistically significant differences at the significance level (a = 0.05) about the challenges and obstacles facing the challenge schools in the northern Palestinian valleys, as seen by the teachers of these schools, due to the educational qualification variable.* It was also found that there were no statistically significant differences at the significance level (a = 0.05) about the challenges and obstacles facing the challenge schools in the northern Palestinian valleys, as seen by the teachers of these schools, due to the variable of teaching experience.In light of the results obtained, the researcher recommended the following:- Providing internet and communication services for challenge schools.Providing secure transportation for students and teachers.Providing protection means for students, teachers and the school.Providing governmental and local financial support for the school.- Drawing the attention of the international community to the suffering of these schools and mobilizing the world for them.